Optimasi Penggunaan Kembali Limbah Karbon Aktif Industri Vetsin Sebagai Biochar Menggunakan Taguchi Orthogonal Array L4: Optimising The Reuse Of Vetsin Industry Activated Carbon Waste As Biochar Using The Taguchi Orthogonal Array L4 - Setiyo Irnanto, Anggra; Handoko, Fourry; Laksmana, Dimas Indra (Gontor Agrotech Science Journal, 2024)
PT XY is a company producing vetsin in the food industry. The company makes extensive use of material resources for its industrial development, which has an impact on the environment. Waste-activated carbon is the result of the color absorption process of the solution. The problem is that the waste generated causes pollution to the company's environment and cannot be stored for long. The average carbon waste generated from January to December 2023 is 86.40 tonnes. Therefore, it is necessary to reuse activated carbon waste into biochar or carbon fertilizer. Processing strategy by conducting experiments using the Taguchi method. Problem identification with an approach that refers to the Responsible Waste Management Hierarchy, and limits the implementation of experiments to the principle of reuse. The Taguchi Orthogonal Array L4 method was chosen for the experimental design because it is more cost-effective than other DOEs and the signal noise is predictable. This research was conducted through experimental methods to know the effect of biochar planting media from activated carbon waste on the growth of kale plants (gr) and get optimal composition variations. As a result, an optimization design was obtained with wet carbon waste material, 25% biochar concentration, and bright light conditions, with an n-gain value of 4.49 resulting in a high improvement category. Comparison of biochar quality with Charcoal Powder from Workplant Store by SNI 06-3730-1995 standard. In biochar products from activated carbon waste, there is a glutamate content of 0.345 g/dL which is a good amino acid for plant growth.